2023
DOI: 10.3389/fmed.2023.1073025
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pemafibrate on liver enzymes and shear wave velocity in non-alcoholic fatty liver disease patients

Abstract: Background/AimsPemafibrate is a selective peroxisome proliferator-activated receptor α modulator that improves serum alanine aminotransferase (ALT) in dyslipidemia patients. Pemafibrate was reported to reduce ALT in non-alcoholic fatty liver disease (NAFLD) patients, but efficacy was not clearly elucidated due to the small size of previous study populations. Therefore, we explored pemafibrate efficacy in NAFLD patients.MethodsWe retrospectively evaluated pemafibrate efficacy on liver enzymes (n = 132) and live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 38 publications
5
18
0
Order By: Relevance
“…For example, a randomized trial 19 of 118 patients with magnetic resonance imaging-diagnosed NAFLD, including patients without dyslipidemia, demonstrated that pemafibrate treatment over 72 weeks did not improve magnetic resonance imaging-estimated proton density fat fraction, but it did lead to improvements in ALT and GGT levels and magnetic resonance elastography-based liver stiffness at 48 weeks and at 72 weeks. Several other studies of pemafibrate treatment have reported improved fibrosis using non-invasive tests, including analyses of Mac-2 binding protein glycosylation isomer 20 and shear wave velocity, 16 and the results of these studies support the present results.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…For example, a randomized trial 19 of 118 patients with magnetic resonance imaging-diagnosed NAFLD, including patients without dyslipidemia, demonstrated that pemafibrate treatment over 72 weeks did not improve magnetic resonance imaging-estimated proton density fat fraction, but it did lead to improvements in ALT and GGT levels and magnetic resonance elastography-based liver stiffness at 48 weeks and at 72 weeks. Several other studies of pemafibrate treatment have reported improved fibrosis using non-invasive tests, including analyses of Mac-2 binding protein glycosylation isomer 20 and shear wave velocity, 16 and the results of these studies support the present results.…”
Section: Discussionsupporting
confidence: 90%
“…16 In terms of the use of baseline parameters to predict pemafibrate response, age and TG level have been reported to be associated with normalization of ALT. 16 Despite these connections to markers of fibrosis, to our knowledge, few studies have examined factors at baseline that directly contribute to improvement of fibrosis. Over a 6-month pemafibrate treatment, Shinozaki et al reported that age greater than 50 years and BMI less than 25 contributed to reduction of levels of Mac-2 binding protein glycan isomer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, pemafibrate could be a promising therapeutic agent for NAFLD and NASH as well as a candidate for combination therapy with statins or other lipid-lowering drugs. Numerous studies in the literature have demonstrated that pemafibrate significantly improves liver function, serum TG and liver stiffness in NAFLD patients [ 109 ]. Moreover, pemafibrate improves markers of hepatic inflammation and fibrosis regardless of BMI.…”
Section: Sex- and Gender-related Differences In The Management Of Chr...mentioning
confidence: 99%